Computational drug discovery of potential 5α-reductase phytochemical inhibitors and hair growth promotion using in silico techniques - Behnam Hasannejad-Asl; Behnam Hasannejad-Asl; Farkhondeh Pooresmaeil; Sareh azadi; Ali Najafi; Ali Esmaeili; Saeid Bagheri-Mohammadi; Bahram Kazemi (Frontiers in Bioinformatics)
IntroductionMale pattern hair loss (MPHL), also known as androgenetic alopecia (AGA), is a common disorder primarily caused by dihydrotestosterone (DHT). The Food and Drug Administration (FDA) has approved two 5-alpha reductase (5-AR) inhibitors—finasteride and dutasteride—for treating this condition. However, recent studies have reported adverse sexual side effects and issues with sperm production in young men using these medications. There are also recommendations for effectively treating hair loss with natural remedies, such as Urtica dioica (nettle), Serenoa repens (saw palmetto), and Trigonella foenum-graecum (fenugreek) that is mainly used for diminish the hair loss in the traditional medicine. Research shows that these herbal formulations and plant extracts may help reduce hair loss. However, the concentration of active compounds in these herbal extracts is often low, necessitating a large extract volume to achieve noticeable effects on hair growth. Although many studies have investigated the effects of these herbal extracts on hair growth, fewer studies focus on the specific compounds influencing the molecular mechanisms of hair loss, particularly the inhibition of 5-AR.MethodsFor the first time, we aimed to applied a computational study to explore the phytochemicals extracted from these herbs to identify compounds that can effectively bind to and inhibit 5-AR. Additionally, we assessed the stability of the ligands encapsulated in lipid nanoparticles (LNP) by conducting molecular dynamics (MD) simulations of the LNP-encapsulated ligands. We utilized an online database to identify compounds from the extracts of nettle, saw palmetto, and fenugreek. We then analyzed their binding affinity to 5-AR using computational techniques.ResultsWe found that 6 molecules—Jamogenin, Neodiosgenin, Chlorogenic acid, Rutin, Riboflavin, and Ursolic acid—are effective in binding to 5-AR. Additionally, our in silico studies revealed that vesicle-entrapped JAMOGENIN, which has a stronger bond with 5-AR, is more stable than its unencapsulated form.DiscussionTherefore, these 6 molecules, particularly JAMOGENIN, should be considered for experimental analysis in both their unencapsulated and nanocarrier-encapsulated states to promote hair follicle growth.